A technique to establish liquid ethanol tubular combustion by dual swirl. (15th May 2022) - Cao, Qing; Xie, Dingjiang; Wang, Kuanyu; Wang, Ningfei; Shi, Baolu
Highlights: A compact, robust and clean combustion technique is proposed to burn liquid ethanol. A steady ethanol/air tubular flame is established in a dual swirl combustor up to 10 kW. Flame anchoring appears as global equivalence ratio at fuel nozzle exit is below 11. Abstract: This study proposes a compact dual swirl combustor to establish a steady liquid ethanol tubular flame, in which tangential air is injected through two stages. The outer intense swirl induces reversed flame on the surface wall of a concentric copper tube, and the central liquid fuel is heated to vaporize through the inner swirling air inside the copper tube. By enhancing the heat transfer process and promoting the mixing of the reactant, the overall heat output approaches 10 kW, much higher than the original combustor. With temperature measurement and heat transfer analysis, the flame stabilization mechanism has been elucidated. Two kinds of typical flame structures, a tubular flame and an anchored conical flame, have been obtained under various operating conditions. As the flow rate of inner air gradually increases, plenty of the heat aiming to vaporize the liquid fuel is taken off by the air flow, and small droplets occasionally appear downstream the nozzle; furthermore, the global equivalence ratio ( Φ gl ) at the nozzle exit gradually decreases, and an anchored flame appears, which interrupts the fuel mixing with outer swirling air, resulting in soot formation in some cases. Plenty of tests illustrates that as Φ gl is below 11, the flame anchoring will appear.